Addenda to “The Maltese and Sicilian Component in the Arabic Glosses of the Italian version of Maqrē Dardĕqē” - Burgaretta, Dario (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2024)
In un articolo pubblicato nel 2018 (D. Burgaretta, “The Maltese and Sicilian Component in the Arabic Glosses of the Italian Version of Maqrē Dardeqē”, in G. Mandalà, I. Peréz Martín, a cura di, Multilingual and Multigraphic Manuscripts and Documents of East and West, Gorgias Press, Piscataway nj: 233-292), l'Autore ebbe modo di presentare una selezione di glosse arabe dall'edizione italiana del Maqrē Dardĕqē, il glossario biblico trilingue stampato per la prima volta a Napoli nel 1488, basato su un manoscritto datato tra il XIV e il XV secolo, del lessicografo franco-catalano Pereṣ Trebot (Parigi, Bibliothèque nationale de France, ms. Héb. 1243). In questo nuovo articolo vengono presentate ulteriori glosse che non è stato possibile includere nella precedente pubblicazione. Tali integrazioni sono state raccolte e analizzate secondo gli stessi parametri del primo contributo, al fine di ampliare e arricchire il corpus lessicale, nella prospettiva di un'edizione completa delle glosse arabe del Maqrē Dardĕqē italiano. In an article published in 2018 (D. Burgaretta, “The Maltese and Sicilian Component in the Arabic Glosses of the Italian Version of Maqrē Dardeqē”, in G. Mandalà, I. Peréz Martín, eds., Multilingual and Multigraphic Manuscripts and Documents of East and West, Gorgias Press, Piscataway nj: 233-292), the Author presented a selection of Arabic glosses from the Italian edition of the Maqrē Dardĕqē, the trilingual biblical glossary first printed in Naples in 1488, based on a manuscript prototype written between the 14th and 15th centuries by the French-Catalonian lexicographer Pereṣ Trebot (Paris, Bibliothèque nationale de France, ms. Héb. 1243). In this new paper some further glosses, which could not be included in the previous publication, are presented. These additions are collected and analysed according to the same parameters of the first contribution, in order to expand and enrich the corpus, in the perspective of a comprehensive edition of the Arabic glosses of the Italian Maqrē Dardĕqē.